2016
DOI: 10.1108/tpm-05-2016-0021
|View full text |Cite
|
Sign up to set email alerts
|

How staff experience teamwork challenges in a new organizational structure

Abstract: Purpose This study aims to explore challenges arising from the development of teamwork in a new organizational structure, based on the experiences of the staff involved. Design/methodology/approach An explorative and qualitative approach was used, with individual interviews as the data collection method. These interviews were analyzed using qualitative and interpretative analysis with a modified editing style. Findings The results describe how the lack of essential organizational prerequisites for teamwork… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The recognition and use of teams in the workplace has expanded significantly as a response to the competitive, complex and dynamic nature of today's corporate world (Sandoff and Nilsson, 2016;Pina et al, 2008). With advancements in information technologies and globalisation, the capabilities of organisations have equally extended their requirements to modify their team-based structures from purely traditionally co-located arrangements to more virtual settings.…”
Section: Introductionmentioning
confidence: 99%
“…The recognition and use of teams in the workplace has expanded significantly as a response to the competitive, complex and dynamic nature of today's corporate world (Sandoff and Nilsson, 2016;Pina et al, 2008). With advancements in information technologies and globalisation, the capabilities of organisations have equally extended their requirements to modify their team-based structures from purely traditionally co-located arrangements to more virtual settings.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of previous research pointed out the impact of top management support on several work attributes, including OL (Andrianova and Antonacopoulou, 2020; Ellström and Ellström, 2018; Vegchel et al , 2005). Sandoff and Nilsson (2016) described how the lack of essential organizational prerequisites for teamwork and the absence of the leadership qualities needed to facilitate teamwork contribute to difficulties in working in a team-orientated way. They argued that without a team leader support, teamwork is difficult to uphold because the members will need to seek support elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…Another study exploring municipal development leaders' efforts while working with sustainable development showed the importance of communication and collaboration when working as a team "against the grain" in a hierarchical organizational structure (Sandoff and Nilsson, 2016). The study showed how important leadership is in promoting satisfactory communication and collaboration among those involved in striving towards new, challenging goals and ways of working.…”
Section: Discussionmentioning
confidence: 99%